Experimental Demonstration of X-Ray Fluorescence CT Using a Spatially Distributed Multi-Beam X-Ray Source - Chen, Zhiqiang; Zhang, Siyuan; Li, Liang (Frontiers in Physics, 2020)
X-ray fluorescence computed tomography (XFCT) is a high-sensitivity imaging modality for high-atomic elements such as gadolinium (Gd) or gold (Au). In order to improve the contrast of x-ray fluorescence (XRF) signals in the raw projection data, common XFCT systems use single-pixel x-ray spectrometers to record XRF photons stimulated by the pencil-beam x-ray source and achieve line-by-line scan of the whole object by translating the x-ray source or the object. However, this kind of design results in waiting time of the translation device. One improvement would be to replace the traditional x-ray tube with a spatially distributed multi-beam x-ray source and scan the whole object by switching the exposure of each focus. In this study, we present a design of the XFCT system using a spatially distributed multi-beam source, and a XFCT imaging experiment was performed to investigate its feasibility. Each cold cathode of the x-ray source used in this study was made of carbon nanotubes, and each focus was independently controlled by the electronic control system. The incident beam was collimated by a pinhole array to produce a pencil-beam source. The object scanned by the system was a polymethyl methacrylate (PMMA) cylinder (8 cm in diameter) with Gd (20 mg/ml) and I (100 mg/ml) insertions. Results show that the distribution of iodine (I) and Gd in a PMMA phantom was successfully reconstructed, but the imaging performance was limited by the collimation and exposure mode of the current distributed x-ray source. The practicality of the current distributed x-ray source used for XFCT scan and further optimization of the proposed system are discussed according to the experimental results.